Concurrent Mastoid Cellulitis and Langerhans Cells Histiocytosis: A Challenging Diagnosis - Ong, Hui Yan; Goh, Liang Chye; Santhi, Kalimuthu; Sha’ariyah, Mohamad Mokhtar (Oman Medical Specialty Board, 2018)
Langerhans cell histiocytosis (LCH) is a rare proliferative disorder, which commonly arises in the bone and may involve other systems. To date, the diagnosis of temporal bone LCH remains a challenge as it may masquerade as a common ear infection. We report a case of a child who presented to us with persistent bilateral ear discharge for four months and was not responding to treatment. Her condition subsequently worsened, with clinical features and radiological findings suggestive of mastoid cellulitis. Nevertheless, further histopathology study revealed LCH.